2021
DOI: 10.3389/fpls.2021.737004
|View full text |Cite
|
Sign up to set email alerts
|

PacBio and Illumina RNA Sequencing Identify Alternative Splicing Events in Response to Cold Stress in Two Poplar Species

Abstract: In eukaryotes, alternative splicing (AS) is a crucial regulatory mechanism that modulates mRNA diversity and stability. The contribution of AS to stress is known in many species related to stress, but the posttranscriptional mechanism in poplar under cold stress is still unclear. Recent studies have utilized the advantages of single molecular real-time (SMRT) sequencing technology from Pacific Bioscience (PacBio) to identify full-length transcripts. We, therefore, used a combination of single-molecule long-rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…This led to more increment of transcriptome diversity and complexity in SLH and probably contributed to its adaptation to cold stressful condition. Previous reports also had showed that AS events were regulated by multiple environmental stress and were largely associated with cold stress resistance in plants ( Li et al., 2020b ; John et al., 2021 ; Yang et al., 2021 ). In agreement with other plant species, the predominant AS events were IR in peanut.…”
Section: Discussionmentioning
confidence: 88%
“…This led to more increment of transcriptome diversity and complexity in SLH and probably contributed to its adaptation to cold stressful condition. Previous reports also had showed that AS events were regulated by multiple environmental stress and were largely associated with cold stress resistance in plants ( Li et al., 2020b ; John et al., 2021 ; Yang et al., 2021 ). In agreement with other plant species, the predominant AS events were IR in peanut.…”
Section: Discussionmentioning
confidence: 88%
“…AS mainly involve SFs interacting with RNA-binding proteins at regulatory sites known as silencers or enhancers. 42 SFs promote or inhibit splicing events by recognizing splicing regulatory sites on precursor RNA and recruiting and assembling spliceosomes. 43 SFs have become a new class of oncoproteins.…”
Section: Discussionmentioning
confidence: 99%
“…It increases the chances for discovering new genes and detecting AS events, APA, as well as lncRNAs. The combined application of second- and third-generation sequencing technologies has emerged as a powerful tool in transcriptomics research, successfully revealing transcriptome and gene structure information in multiple plant species [ 22 25 ].…”
Section: Introductionmentioning
confidence: 99%